The introduction of institution of «peasant сhief» in the Steppe region in the early ХХ century - V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
The article examines the activities of administrative institutions of the Steppe region in solving problems related to the organization of peasant self-government. Attention is drawn to the introduction of the institution of peasant leaders who had the right to supervise all peasant social administration. Information on the activities of the indispensable members on peasant affairs of the regional boards is given